Mixed Reality for a collective and adaptive mental health metaverse - Navas-Medrano, Samuel; Soler-Dominguez, Jose L.; Pons, Patricia (Frontiers in Psychiatry, 2024)
This research paper explores the significant transformative potential of Mixed Reality (MR) technology as enabler of the metaverse, specifically aimed at enhancing mental health therapies. The emerging world of the metaverse, a multiuser, adaptive, three-dimensional digital space, paired with the interactive and immersive benefits of MR technology, promises a paradigm shift in how mental health support is delivered. Unlike traditional platforms, MR allows for therapy within the comfort of the user's familiar surroundings, while incorporating the benefits of social collaboration and interactions. The metaverse environment fosters heightened personalization and deeper user engagement, thereby offering a more tailored approach to computerized therapy. Beyond its immersive capabilities, MR offers potential for real-time, smart adaptations to the users' psycho-physiological state, targeting unique patients' needs on a diverse spectrum of therapeutic techniques, thus broadening the scope of mental health support. Furthermore, it opens avenues for continuous emotional support in everyday life situations. This research discusses the benefits and potentials of integrating MR within a mental health metaverse, highlighting how this innovative approach could significantly complement traditional therapeutic methods, fostering improved treatment efficacy, focusing on social and collective experiences, and increasing patient engagement.